GI Surgery Annual Volume 24 (GI Surgery Annual,, 2018)
The 24th volume of this highly successful series includes new contemporary topics such as corrosive injuries of the oesophagus, post-gastrectomy complications, advances in imaging of inflammatory bowel disease, unusual presentations of gallstones, gall bladder cancer with jaundice, minimally invasive pancreatic surgery, and enhanced recovery after surgery. Finally, the chapter on advances in GI surgery, like in each past volume, reviews important new developments in the field. The GI Surgery Annual 24th Volume provides an overall roundup of selected topics that were deemed particularly relevant and topical by the series editors. .